Assessment of the cochlear implant pathway for newborn hearing screening referrals. (2nd November 2021) - Mathew, Rajeev; Bajo, Fernando Rodriguez; Hatton, Nicola; Buttfield, Louise; Gowrishankar, Shravan; Vickers, Deborah; Donnelly, Neil; Tysome, James; Bance, Manohar; Axon, Patrick
Abstract : Objective: To evaluate the cochlear implant (CI) assessment pathway for children referred through the newborn hearing screening programme (NHSP) and identify potential reasons for delay in CI surgery at a large UK centre. Methods: Retrospective analysis of electronic notes of children referred through NHSP from 2016 to 2019. Key points in the assessment pathway from referral to switch-on were assessed. Results: Of the 46 referrals, 44 went on to have CI surgery. Median age at CI surgery was 15 months (interquartile range (IQR) 13 to 17 months). Only 5% of referrals were implanted before the age of 12 months. Delayed referral and the presence of otitis media with effusion (OME) were associated with delayed implantation. The median period of monitoring for OME was 48 days (IQR 20 to 93 days), with a natural resolution rate of only 11%. The median time from surgery to switch-on was 5 weeks (IQR 4.1 to 5.4 weeks). Conclusion: Achieving implantation prior to the age of 12 months for NHSP referrals can be challenging for a variety of reasons. The delays in the system and the steps that our implant programme has taken to address these will be highlighted.